What are the New Functions of Agriculture Cooperatives in the Progress of Globalization? The Case of Agriculture Cooperatives of Kastamonu - Yücel, Mustafa; Aktaş, Yaşar; Taner, Neslişah (Eurasian Economists Association, 2015)
While production and markets have been becoming more integrated since barriers to the international trade reduced, capital movements and the speed of spreading of technology increased with the progress of globalization, issues regarding to agriculture, environment, women, employment, and education became more critical. In this research, “by which functions and missions can agricultural cooperatives sustain their assets under globalized conditions” is the major research question. In the research, 19 cooperatives were chosen among 308 cooperatives, depending on their distance to Kastamonu, foundation year, and the amount of member. Subjects were determined by their traits and occupations. 164 subjects were interviewed via survey questions in 2014-2015. In research, “The situation-specific approach” model, developed by Hartmut Albrecht was applied. Because of the progress of change in organizational values, agriculture cooperatives have to undertake new functions in addition to maintaining agricultural production. The functions can be classified into 4 categories as socio-economic (taking local goods to international markets, recording incomes in the agriculture sector, and creating new employment positions to reduce migration to urban), international relations (developing new projects toward internationalizing to collaborate with other cooperatives), planning (making long-term strategic plans), and education (training women in rural areas, and obtaining their collaboration in cooperative campaigns, and educating future's cooperative managers).
Keywords: 2. Zero hunger; 5. Gender equality; 9. Industry and infrastructure; 8. Economic growth; 11. Sustainability; 1. No poverty; 16. Peace & justice; 12. Responsible consumption